You should write `tan x` as `tan 2(x/2)` such that:

`tan x = tan(x/2 + x/2)`

Using the formula `tan(a+b) = (tan a + tan b)/(1 - tan a*tan b)` yields:

`tan(x/2 + x/2) = (tan (x/2) + tan (x/2))/(1 - tan^2 (x/2))`

`tan x = (2 tan(x/2))/(1 - tan^2 (x/2))`

Since the problem provides the information that `tan(x/2) = t` yields:

`tan x = (2t)/(1 - t^2)`

You need to express `tan 2x` such that:

`tan 2x = tan(x + x)`

`tan(x + x) = (tan x + tan x)/(1 - tan^2 x)`

`tan(x + x) = (2tan x)/(1 - tan^2 x)`

`tan 2x = (2*(2t)/(1 - t^2))/(1 - ((2t)/(1 - t^2))^2)`

`tan 2x = ((4t)/(1 - t^2))/(1 - (4t^2)/(1 - t^2)^2)`

`tan 2x = ((4t)/(1 - t^2))/(((1 - t^2)^2 - 4t^2)/(1 - t^2)^2)`

`tan 2x = (4t)(1 - t^2)/((1 - t^2 - 2t)(1 - t^2 + 2t))`

Checking if the equation `tan 2x = 1` may be expressed as `t^4+4t^3-6t^2-4t+1` yields:

`(4t)(1 - t^2)/((1 - t^2 - 2t)(1 - t^2 + 2t)) = 1`

`4t - 4t^3 = (1 - t^2)^2 - 4t^2`

`4t - 4t^3 = 1 - 2t^2 + t^4 - 4t^2`

`4t - 4t^3 = t^4 - 6t^2 + 1`

Moving all terms to one side yields:

`t^4 + 4t^3- 6t^2 - 4t+ 1 = 0`

**Comparing the given equation in t to the equation that results substituting `(4t)(1 - t^2)/((1 - t^2 - 2t)(1 - t^2 + 2t))` for `tan 2x` yields that `t^4 + 4t^3 - 6t^2 - 4t + 1 = t^4 + 4t^3 - 6t^2 - 4t + 1` , hence, the alternative form of the equation `tan 2x = 1` is `t^4 + 4t^3 - 6t^2 - 4t + 1 = 0` .**